Epidemiology of secondary infection after snakebites in center-west Brazil - Soares Coriolano Coutinho, João Victor; Fraga Guimarães, Taiguara; Borges Valente, Bruno; Gomes Martins de Moura Tomich, Lísia (PLoS neglected tropical diseases, 2023)
Snakebites represent a significant health problem in tropical countries, with an annual incidence of 2.7 million cases worldwide. The incidence of secondary infections after snake bites is also high and is usually caused by bacteria from the oral cavity of snakes. Morganella morganii has been identified as an important cause of infections and has been guiding antibiotic therapy in several regions of Brazil and the world. We performed a retrospective cross-sectional evaluation of snakebites in hospitalized patients between January 2018 and November 2019 and selected those with secondary infection in their medical records. During the period, 326 cases of snakebites were treated, and 155 (47.5%) of them eventually had secondary infections. However, only seven patients underwent culture of soft tissue fragments, in which three cases were negative culture results, while Aeromonas hydrophila was identified in four cases. Of these, 75% were resistant to ampicillin/sulbactam, 50% had intermediate sensitivity to imipenem, and 25% had intermediate sensitivity to piperacillin/tazobactam. Trimethoprim/sulfamethoxazole (TMP-SMX) was not tested on any strain. Of the 155 cases that progressed to secondary infections, 48.4% (75) were empirically treated with amoxicillin/clavulanate, 41.9% (65) with TMP-SMX, and 32 (22%) of these 144 cases required a change to a second regimen, and 10 of these 32 patients required a third therapeutic regimen. Wild animals act as reservoirs of resistant bacteria because their oral cavity favors biofilm formation, which explains the finding of A. hydrophila with a reduced sensitivity profile in this study. This fact is essential for the appropriate choice of empirical antibiotic therapy.